CHANGES IN THE CD68+ EXPRESSION OF THE INTERSTITIAL ENDOCRINE CELLS DURING CENTRAL BLOCKAGE OF THE HYPOTHALAMUS WITH TRIPTORELLIN AND THE ADDITION OF QUERCETIN IN RATS’ TESTES - Stetsuk, Ye.V.; Shepitko, V.I.; Boruta, N.V.; Rud, M.V.; Sokolenko, V.M. (World of Medicine and Biology, 2024)
The purpose of the study was to establish quantitative changes in the expression of CD68+ cells in the interstitial space and vessels of the testes under conditions of central blockade of luteinizing hormone synthesis by triptorelin with the addition of quercetin to the diet. The study was conducted on 35 sexually mature white male rats. The experimental group’s animals were injected with a solution of triptorelin acetate at a rate of 0.3 mg of the active substance per kg of animal weight to simulate the central deprivation of the luteinizing hormone synthesis with the addition of quercetin. The central effect of blocking the synthesis of luteinizing hormone by triptorelin in the hypothalamus leads to an increasing increase in the distribution of the CD68 receptor in the interstitial space and in the vessels of the testis from the 30th to the 180th day of the experiment with a gradual decrease to the control indicators on the 365th day of observation. Adding the riboflavonoid quercetin to the diet significantly reduces oxidation processes and reduces triptorelin’s negative impact on testicular tissue.